Reaping disease-free stone fruits - Attri, B L; Kumar, Anil; Kishor, Arun; Ahmed, Nazeer (Indian Horticulture, 2015)
An economic loss of 15-20% has been estimated due to various post-harvest diseases in stone fruits. If suitable control measures are not adopted timely, losses may increase up to 40-50%. It not only makes the produce unsaleable but is also responsible for huge monetary loss to growers. Therefore, prophylactic measures should include keeping the fruit-bearing plants free from various fungal attacks following some strategies.